FAKTOR YANG MEMPENGARUHI KURANGNYA KEAKTIFAN PESERTA DIDIK DALAM KEGIATAN PEMBELAJARAN DI KELAS (Jurnal Sosial Humaniora dan Pendidikan, 2023)
This research aims to determine the factors that influence students' lack of activeness in learning activities. The type of research used in this research is qualitative research, and the results of the research are: First, the internal factors that influence the learning activity of class IX students at SMP Negeri 2 Waigete are physiological and psychological factors. Second, external factors that influence the learning activity of class IX students at SMP Negeri 2 Waigete are non-social factors, namely place and facilities, as well as social factors, namely teachers and peers.